Subsistence harvests of bowhead whales (Balaena mysticetus) at Kaktovik, Alaska (1973-2000) - Koski, William R.; George , John C.; Sheffield , Gay; Galginaitis , Michael S. (J. Cetacean Res. Manage., 2023)
Kaktovik is a small community located on Barter Island in the extreme northeast of Alaska. The bowhead whale hunt is important to the community from both an economic and cultural perspective. Harvests were generally 1-2 bowheads per year in 1973-1988 and 2-4 bowheads per year in 1989-2000. The hunt normally begins on the first Monday in September and historically 83% of harvested whales have been taken in September. In recent years, typical harvest dates have been significantly earlier even though the quota and number of whales taken have increased. The core whaling area extends from 15km west to 25km east of Kaktovik, and offshore as far as 32km. Most whales have been taken within 30km of the village and the mean distance of harvest locations from Kaktovik has not changed from the 1970s to present. Whaling captains select small whales over large whales and there has been a marginally significant decrease in the average size of whales harvested from the 1970s to the present. The size of whales harvested does not increase with date, although other data show that smaller whales become less common in the area as the season progresses. Male and female bowhead whales are harvested in very similar numbers, but females make up 67% of whales harvested early in the season and 32% late in the season.